Getting to diversity what works and what doesn't - Dobbin, Frank (Harvard University Press, 2022)
Management experts Frank Dobbin and Alexandra Kalev sift through decades of data to show why workplace diversity training fails and what works. Arguing that it's time to focus on changing systems rather than individuals, the authors make data-driven recommendations for diversifying management and creating workplaces where everyone can thrive